Dance as Cultural Embodiment in Public Space:Performances at Kuala Lumpur International Airport - Lesa Paranti; Sang Woo Ha; Hanafi bin Hussin; Rimasari Pramesti Putri; Nadia Sigi Prameswari; Ani Nur Auliyatun Latifah (Harmonia: Journal of Arts Research and Education, 2026)
Airports are public spaces and gateways into a country or region, and nowadays they have become cultural reflections, turning them into more than just a means of transport. Through a specific focus on dance at Kuala Lumpur International Airport (KLIA), this study aims to explore the significance of these performances in embodying and communicating Malaysian culture for both dancers and airport visitors. This study is qualitative, drawing on ethnochoreology, performance semiotics, and a cultural embodiment perspective. Data were collected through direct observation of dance performances at KLIA, interviews with dancers and performance managers, documentation, and visitor survey data provided by Malaysia Airports. Triangulation was used to enhance the validity of the findings, while analysis techniques were used for data condensation, presentation, and verification. The findings indicate that dance performances at KLIA Airport are organized by airport management. As a multiethnic country, performances are scheduled in accordance with major commemorative events and meticulously designed in terms of themes, dancers, movements, music, costumes, and makeup. The airport transit space serves as the performance setting, adding a distinctive cultural experience for both dancers and visitors. For the dancers, the body becomes a medium for representing cultural codes. Their role extends from executors of choreography to co-authors of meaning and cultural ambassadors. For airport visitors, dance performances offer a culturally embodied experience that remains memorable long after the airport visit. This study contributes to the development of the concept of cultural embodiment by examining dance performance in the context of airport analysis. Dance serves as a conductor of cultural representation, embodied identity, and global audience participation.